Question was to find general solution of dy/dx = (4x+2y-1)^1/2
This is what I did: let z = 4x + 2y -1 therefore z'=4+2y' => y' = z'/2 - 2
Substitute to get z'/2 - 2 = z^(1/2) => z' = 2*z^(1/2) + 4 (A Bernouilli Equation) Dividing thru by z^(1/2) gives
z^(-1/2) * z' = 2 + 4*z^(-1/2)
Now say m = z^(-1/2)
=> m' = (-1/2)*z^(-3/2) => m' = (-1/2)*z^(-1/2)*z^-1
=> 2*m' = -m*z^-1
=> 2*m'/m = z^-1
Now integrating both sides gives
2 ln m = ln z + c
Does this look right? Where do I have to go from here?
2007-10-23
06:55:34
·
2 answers
·
asked by
Unoticed
1
in
Science & Mathematics
➔ Mathematics